Genome-wide analysis defines genetic determinants of MPN subtypes and identifies a sex-specific association at CDH22/CD40 - Tapper, William; Dawoud, Ahmed A. Z.; Score, Joannah; Chase, Andrew J.; Baxter, E. Joanna; Ewing, Joanne; Wallis, Louise; Guglielmelli, Paola; Colomer, Dolors; Bellosillo, Beatriz; Gomez, Montse; Hernández-Boluda, Juan Carlos; et al. (Blood, 2025)
To identify genetic variants that influence myeloproliferative neoplasm (MPN) phenotypes, we undertook a 2-stage patient-only genome-wide association study. MPN subtypes (essential thrombocythemia [ET]; polycythemia vera [PV]) were compared with each other to healthy controls and stratified analyses was performed for chromosome 9p aberrations, JAK2 V617F mutation burden, and sex. The ET vs PV analysis identified known associations: (1) at HBS1L-MYB that increased ET risk (Pmeta = 7.93 × 10-6, odds ratio [OR] = 1.28) and reduced PV risk (Pmeta = 9.43 × 10-5, OR = 0.81) and (2) at GFI1B-GTF3C5 that predisposed to PV only (Pmeta = 1.43 × 10-9, OR = 1.38). Two further linked intronic variants, rs2425786 and rs2425788, at CDH22/CD40 were significant in females only (Pmeta = 2.67 × 10-8), with predisposition to PV (Pmeta = .0006, OR = 1.3) and reduction of ET risk (Pmeta = 7.82 × 10-5, OR = 0.75). A polygenic risk score consisting of 48 variants from 31 loci demonstrated moderate discriminative performance for ET and PV (area under the curve [AUC] = 0.718) and was improved by optimization for disease subtype (AUCET = 0.724 and AUCPV = 0.755). Overall, our results reveal that multiple germline variants influence MPN phenotype, with HBS1L-MYB and a novel sex-specific association with CDH22/CD40 being the strongest determinants.